Effect of Moringa oleifera Lam. Leaf Extract Against Aluminium Chloride Induced Hippocampal Histology and Serum Enzyme activities in adult Wistar rats : M. oleifera Extract Protect against Aluminium Chloride (International Journal of Medical and Surgical Sciences, 2020)
Introduction: Aluminium, a ubiquitous metal implicated in some neurodegenerative diseases is linked to activation of free oxygen species. The antioxidant-rich plants, Moringa oleifera (MO) is reported to protect against Aluminium activities. This study investigated the actions of MO leaf extract (MOLE) against Aluminium chloride (AlCl3 )- induced hippocampal cellular changes and serum levels of alkaline phosphatase (ALP), aspartate transaminase (AST) and alanine transaminase (ALT) in adult Wistar rats. Materials and Methods: Thirty Wistar rats weighing between 150 g and 220 g were grouped (n=5) into; 1-control (5 mL/kg distilled water), 2-AlCl3 (100 mg/kg), 3-low dose MOLE (250 mg/kg), 4-high dose MOLE (1,000 mg/kg), 5-concurrent AlCl3 and low dose MOLE, and 6-concurrent AlCl3 and high dose MOLE. All administrations were by oral gavages for 21 days. On day 22, following deep anaesthesia and cardiac puncture, blood was obtained for serum enzyme analysis, and the brain perfusion fixed, harvested and processed for histological study. Results: Results showed significantly (p < 0.05) higher ALP level in the AlCl3 group compared with the control, as well as the other test groups. However, there was no significant (p > 0.05) AST and ALT levels. The hippocampal CA3 of the AlCl3 group showed hypertrophic cells, with some of the cells having karyorrhectic features. The concurrent AlCl3 and low and high doses, MOLE groups showed less of these adverse features. Conclusion: These results suggest that MOLE may protect enzymatic activities against Aluminium chloride. However, its action on hippocampus is still subject to further investigation.
Keywords: Moringa oleifera, Aluminium chloride, Hippocampal, Neurotoxicity, Serum Enzyme, Histology